Performance of Magnetic Palm Oil Empty Fruit Bunch Biochar for Removal of Waste Cooking Oil - Shahrulzaman, Maimunah; Harun, Hasnida (Progress in Engineering Application and Technology, 2021)
Waste cooking oil is an end-product of oil used for frying or cooking in the manufacturing industry, restaurants and households. Unfortunately, improper disposal of the waste cooking oil in kitchen and sinks will solidify and therefore block the sewer pipes. It may also forms a thin layer above the water that would reduce the dissolved oxygen concentration required for underwater living creatures. In order to remove waste cooking oil from the aqueous system, this research is therefore intended to develop a magnetic palm oil empty fruit bunch biochar. The magnetic biochar was prepared via co-precipitation of FeCl3 and FeSO4 for the formation of iron oxide. Batch experiments were conducted to analyse the performance of the magnetic biochar to remove the waste cooking oil. The magnetic biochar was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). Batch sorption studies were carried out at different parameters which is waste cooking oil concentrations of 0.25, 1.00 and 5.00 % with the magnetic biochar dose at 0.5, 1.0 and 1.5 g and 10, 60 and 120 seconds of contact time. The pH of solutions is in the range of 6.5 to 7.5. Reusability studies were also conducted on magnetic biochar to measure the adsorption capacity. The analysis from FTIR and SEM has proven that magnetic biochar from palm oil empty fruit bunch can act as adsorbent. From the result, the optimum performance of magnetic biochar in removing cooking oil waste is at 0.25 % concentration of waste cooking oil with 1.5 g magnetic biochar and 120 s contact time. The magnetic biochar towards zero waste production could be achieved as the magnetic biochar performance after 3 cycles of adsorption are still promising. As a conclusion, it proved that in oil removal applications, magnetic biochar could be used as a cost-effective and efficient adsorbent.